Effectiveness of Fading Technique on Art Skills (Drawing with Pencils) for PG PAUD Students at the Riau University - Hukmi, Hukmi; Risma, Devi (Proceedings of the UR International Conference on Educational Sciences, 2018)
This research is supported by the problem of art skills of PG PAUD studentsin drawing with pencil are still low. To improve this, an experimental research is carried out by giving treatments in fading techniques: shading techniques, drawing shapes, perspectives, and landscapes. In this research, it can be concluded the findings are: 1) before the provision of fading techniques, basic art skills of PG Riau PAUD students in the category of less than 55.72%; 2) after giving fading technique treatments, art skills of students of the Riau PA PAUD PG are in the good category of 73.57%; 3) after treatment, there is an influence (effectiveness) of fading techniques on art skills (drawing with pencil) forPG PAUD Students at the Riau University which is 40.30%.